The obtaining and properties investigation of plasma formation at pulse discharge in water aerosol - Iukhymenko, V.V.; Fedirchyk, I.I.; Chernyak, V.Ya.; Martysh, E.V.; Fedorovich, O.A.; Lisitchenko, T.E.; Belenok, N.V. (Вопросы атомной науки и техники, 2013)
The results of investigation of electro-physical and spectral properties of the impulse discharge plasma in aerosol were represented in work. The discharge current, voltage and integral spectrum of plasma were measured. The discharge space was filmed with the help of digital camera. The plasmoids with lifetimes about 150 milliseconds in the autonomous stage after current zero were observed.